Cement mortar for ductile iron pipe lining and preparation method thereof
By using modified nanosilicon composites in cement mortar for ductile iron pipe lining, the problem of quality defects in cement mortar lining is solved, and high-quality cement mortar lining is achieved, which improves compressive and flexural strength and reduces production costs.
Patent Information
- Application Number
- CN202411809813.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-08
AI Technical Summary
Ductile cast iron pipes are prone to quality defects in cement mortar lining, such as internal cracks, floating sand, hemp pits, etc., resulting in a decrease in yield and an increase in production costs.
A cement mortar for lining of ductile iron tubes is used, and its formula includes 1000 parts of cement, 1200-2100 parts of fine aggregate, 100-150 parts of fly ash, 5-10 parts of nano-silicon composite and 1-2 parts of water reducer. The nano-silicon composite is modified by mixing nano-lithium silicate with a silicon sol and adding ethanol and silane coupling agent to form a highly reactive nano-silicon composite, which is used to enhance the early strength and compactness of the mortar.
The cement mortar has good fluidity and ease, excellent early strength, compactness and mechanical properties (compressive strength and flexural strength), which reduces the crack defect rate of mortar lining and is suitable for large-scale industrial production.
Smart Images

Figure CN119774970A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement mortar preparation, in particular to a method for preparing cement mortar for ductile iron pipe lining. Background Art
[0002] Ductile iron pipes have been widely used in many fields such as municipal water supply and drainage, gas transmission, heat transmission and industrial pipelines due to their excellent mechanical properties, good corrosion resistance and simple installation method, and have become an indispensable part of modern pipeline systems.
[0003] Cement mortar has become the preferred material for corrosion protection of the inner wall of ductile iron pipes due to its excellent anti-corrosion performance, high bonding strength and smooth and uniform surface formed by the centrifugal coating process. It can release alkaline substances when it comes into contact with water, forming a passivation layer, providing electrochemical protection and effectively preventing corrosion. In addition, cement mortar has strong adaptability and the formula can be adjusted according to water quality conditions to adapt to different corrosive environments. The simple construction and high cost-effectiveness make cement mortar widely used in the anti-corrosion treatment of ductile iron pipes, ensuring the long-term stable operation of pipelines and water quality safety.
[0004] Affected by different environmental factors, ductile iron pipes are prone to cement mortar lining quality defects in the actual production process, which manifest as internal cracks in the lining, floating sand, pits, blistering, and lining wear. Among them, defects such as lining cracks and pits reduce the yield of cement mortar, increase the production cost of cast pipes, and restrict the improvement of the quality of cast pipe products.
[0005] Therefore, there is an urgent need to develop a cement mortar for ductile iron pipe lining that can be used to produce high-quality cement mortar lining under existing production process conditions, reduce quality defects of cement mortar lining, and meet the anti-corrosion requirements of ductile iron pipes. Summary of the invention
[0006] The present invention provides a cement mortar for ductile iron pipe lining and a preparation method thereof, wherein the cement mortar has good fluidity and workability, as well as excellent early strength, compactness and mechanical properties (compressive strength and flexural strength). The present invention is specifically achieved through the following technologies.
[0007] A cement mortar for ductile iron pipe lining, comprising, by weight, 1000 parts of cement, 1200-2100 parts of fine aggregate, 100-150 parts of fly ash, 5-10 parts of nano-silicon composite and 1-2 parts of water reducing agent;
[0008] The nano-silicon composite is prepared by mixing nano-lithium silicate and silica sol in a mass ratio of (0.05-0.3):1, and adding 1-2% of ethanol and 1-5% of silane coupling agent accounting for the total mass of the silica sol for in-situ modification.
[0009] Furthermore, the mass ratio of the nano lithium silicate to the silica sol is 0.2:1.
[0010] Furthermore, the preparation method of the nano-silicon composite is: adding the nano-lithium silicate to the silica sol and mixing evenly, adding ethanol and a silane coupling agent, and keeping the mixture at 45-60° C. for 2-3 h to obtain the nano-silicon composite.
[0011] Furthermore, in the method for preparing the nano-silicon composite, the nano-silicon composite is obtained by keeping the temperature at 50° C. for 2 h.
[0012] Furthermore, the cement is ordinary Portland cement with PO 42.5 and / or PO 52.5.
[0013] Furthermore, the fly ash is Class II fly ash, which is Class F Class II fly ash in GB / T 1596-2017.
[0014] Furthermore, the water reducer is one or more of lignin sulfonate sodium salt, naphthalene-based high-efficiency water reducer, aliphatic high-efficiency water reducer, amino high-efficiency water reducer and polycarboxylic acid high-efficiency water reducer.
[0015] The present invention also provides a method for preparing the cement mortar for ductile iron pipe lining, comprising uniformly mixing cement, fly ash, fine aggregate and water reducing agent to obtain a dry mixture; adding water to a nano-silicon composite and stirring it to obtain a nano-silicon composite solution; adding the nano-silicon composite solution to the dry mixture to obtain a cement mortar for ductile iron pipe lining; and the amount of water added to prepare the nano-silicon composite solution is 0.35-0.5 times the mass of the cement.
[0016] The cement mortar for ductile iron pipe lining provided by the present invention has a raw material nano-silicon composite with high reactivity, which can serve as the nucleation center of CSH (calcium silicate hydrate gel) and react with part of Ca(OH) in the cement hydration product. 2 The reaction generates CSH, which fills the pores of the mortar, which is beneficial to enhance the early strength and density of the mortar, and improve the compressive strength and flexural strength. Water reducer and fly ash can not only greatly reduce the water consumption, but also improve the fluidity and workability of the mortar, and can also participate in the secondary hydration reaction of cement mortar, improving the compressive strength and flexural strength of cement mortar.
[0017] Compared with the prior art, the advantages of the present invention are as follows: the cement mortar for ductile iron pipe lining provided by the present invention has good fluidity and workability, as well as excellent early strength, density and mechanical properties (compressive strength and flexural strength); low production cost, simple and easy process, good repeatability, and is suitable for large-scale industrial production needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The present invention is a schematic diagram of the preparation process of cement mortar for ductile iron pipe lining. DETAILED DESCRIPTION
[0019] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In some implementation cases of the present invention, the provided cement mortar for ductile iron pipe lining comprises raw materials, in parts by mass, of 1000 parts of cement, 1200-2100 parts of fine aggregate, 100-150 parts of fly ash, 5-10 parts of nano-silicon composite and 1-2 parts of water reducer.
[0021] The nano-silicon composite is prepared by mixing nano-lithium silicate and silica sol in a mass ratio of (0.05-0.3):1, and adding 1-2% of ethanol and 1-5% of silane coupling agent to form an in-situ modified silica sol.
[0022] Lithium silicate is a nanoscale Li-ion product produced by the reaction of lithium hydroxide and silica sol. 2 O·nSiO 2 , also known as lithium water glass. Lithium silicate has excellent bonding strength and reactivity, low viscosity and easy penetration. The lithium silicate used in the present invention is produced by Haining Lingzhong New Materials Technology Co., Ltd.
[0023] Silica sol is a cheap colloidal solution of nanometer-level inorganic polysilicic acid with water as a dispersion medium. The particles of silica sol are fine and the particle size is nanometer-level. The silica sol used in the present invention can be directly purchased from commercially available silica sol products.
[0024] The fine aggregate selected in the present invention is common types of fine aggregate such as river sand, machine-made sand, quartz sand, etc.; granular materials made by secondary processing of waste building materials, etc. can also be selected.
[0025] Optionally, the mass ratio of the nano lithium silicate to the silica sol is: (0.05-0.3):1.
[0026] Specifically, the preparation method of the nano-silicon composite is: adding the nano-lithium silicate to the silica sol and mixing evenly, adding ethanol and a silane coupling agent, and keeping the mixture at 45-60° C. for 2-3 h to obtain the nano-silicon composite.
[0027] Optionally, in the method for preparing the nano-silicon composite, the nano-silicon composite is obtained by keeping the temperature at 50° C. for 2 h.
[0028] Optionally, the cement is ordinary Portland cement of PO 42.5 and / or PO 52.5.
[0029] Optionally, the fly ash is Class II fly ash, which is Class F Class II fly ash in GB / T 1596-2017.
[0030] Optionally, the silane coupling agent may be one of common silane coupling agents such as γ-aminopropyltriethoxysilane, γ-glycidyltriethoxysilane, γ-glycidoxybutyltrimethoxysilane, and glycidoxymethyltriethoxysilane.
[0031] Optionally, the water reducer is one or more of sodium lignin sulfonate, naphthalene-based high-efficiency water reducer, aliphatic high-efficiency water reducer, amino high-efficiency water reducer and polycarboxylic acid high-efficiency water reducer.
[0032] In some other embodiments of the present invention, the preparation method of cement mortar for ductile iron pipe lining is:
[0033] (1) Cement, fly ash, fine aggregate and water reducing agent are uniformly mixed to obtain a dry mix; water is added to the nano-silicon composite and stirred to obtain a nano-silicon composite solution; the amount of water added to prepare the nano-silicon composite solution is 0.35-0.5 times the mass of the cement.
[0034] (2) Adding the nano-silicon composite solution to the dry mix to obtain cement mortar for ductile iron pipe lining.
[0035] Example 1
[0036] The cement mortar for ductile iron pipe lining provided in this embodiment comprises, in parts by mass, 1000 kg of P.O. 42.5 ordinary Portland cement, 1200 kg of fine aggregate, 100 kg of fly ash, 5 kg of nano-silicon composite and 1 kg of water reducer.
[0037] The preparation method of the nano-silicon composite selected in this embodiment is: under the premise of continuous stirring, 2 kg of nano-lithium silicate is slowly added to 10 kg of silica sol and mixed evenly; then 1 kg of ethanol and 1 kg of silane coupling agent are added, and the mixture is kept warm at 50° C. for 2 h to obtain the nano-silicon composite.
[0038] The sources of the raw materials used in the preparation of cement mortar for ductile iron pipe lining in this embodiment are shown in Table 1 below.
[0039] Table 1 Raw material information of cement mortar for ductile iron pipe lining
[0040]
[0041] The cement mortar for ductile iron pipe lining of the present embodiment is prepared by the following method:
[0042] (1) Cement, fine aggregate, fly ash and polycarboxylate water reducer were added to a mixing tank and dry mixed for 10 min to obtain a dry mix; nano-silicon composite was weighed and added to 386 kg of water and stirred thoroughly to obtain a nano-silicon composite solution.
[0043] (2) Add the nano-silicon composite solution to the dry mixture and stir it thoroughly to obtain a finished cement mortar for ductile iron pipe lining.
[0044] Example 2
[0045] The cement mortar for ductile iron pipe lining provided in this embodiment comprises, in parts by mass, 1000 kg of P.O. 42.5 ordinary Portland cement, 2100 kg of fine aggregate, 150 kg of fly ash, 10 kg of nano-silicon composite and 2 kg of water reducer.
[0046] The preparation method of the nano-silicon composite selected in this embodiment is: under the premise of continuous stirring, 0.5 kg of nano-lithium silicate is slowly added to 10 kg of silica sol and mixed evenly; then 2 kg of ethanol and 5 kg of silane coupling agent are added, and the mixture is kept warm at 60° C. for 2 h to obtain the nano-silicon composite.
[0047] In this embodiment, the amount of water added when preparing cement mortar for ductile iron pipe lining is 410 kg, which is 0.41 times the mass of cement.
[0048] The preparation method of cement mortar for ductile iron pipe lining provided in this embodiment is the same as that in Example 1.
[0049] Example 3
[0050] The raw materials and dosage of cement mortar for ductile iron pipe lining provided in this embodiment are the same as those in Example 1. The difference is that the nano-silicon composite selected in this embodiment is prepared by: slowly adding 3 kg of nano-lithium silicate to 10 kg of silica sol under constant stirring, and mixing evenly; then adding 2 kg of ethanol and 3 kg of silane coupling agent, and keeping warm at 45°C for 3 h to obtain the nano-silicon composite.
[0051] In this embodiment, the amount of water added when preparing cement mortar for ductile iron pipe lining is 410 kg, which is 0.41 times the mass of cement.
[0052] The preparation method of cement mortar for ductile iron pipe lining provided in this embodiment is the same as that in Example 1.
[0053] Comparative Example 1
[0054] The cement mortar provided in this comparative example comprises, by mass, 1000 kg PO 42.5 ordinary Portland cement, 1200 kg fine aggregate, 100 kg fly ash, 0.714 kg nano-lithium silicate, 3.571 kg silica sol, 0.357 kg silane coupling agent, 0.357 kg ethanol and 1 kg water reducing agent.
[0055] The preparation method of the cement mortar of this comparative example is: add all the above raw materials except the water reducing agent into a mixing tank, dry mix and stir for 10 minutes; then add 1 kg of water reducing agent and 386 kg of water, stir well, and obtain a finished cement mortar.
[0056] Comparative Example 2
[0057] The cement mortar provided in this comparative example comprises, in parts by mass, 1000 kg PO 42.5 ordinary Portland cement, 1200 kg fine aggregate, 5 kg nano-silicon composite and 1 kg water reducing agent.
[0058] The preparation method of the nano-silicon composite of this comparative example is the same as that of Example 1. The preparation method of cement mortar is:
[0059] (1) Cement, fine aggregate and polycarboxylate water reducer were added to a mixing tank and dry mixed for 10 min to obtain a dry mix. Nano-silicon composite was weighed and added to 386 kg of water and stirred thoroughly to obtain a nano-silicon composite solution.
[0060] (2) Add the nano-silicon composite solution to the dry mixture and stir it thoroughly to obtain a finished cement mortar for ductile iron pipe lining.
[0061] Comparative Example 3
[0062] The cement mortar provided in this comparative example comprises, in parts by mass, 1000 kg PO 42.5 ordinary Portland cement, 1200 kg fine aggregate, 100 kg fly ash and 1 kg water reducing agent.
[0063] The preparation method of cement mortar is as follows: weigh the above raw materials, add them into a mixing tank, dry mix and stir for 10 minutes to obtain a dry mixture; weigh 391 kg of water, add it into the dry mixture and stir it thoroughly to prepare a finished cement mortar for ductile iron pipe lining.
[0064] Comparative Example 4
[0065] The cement mortar provided in this comparative example uses 1000 kg PO 42.5 ordinary Portland cement, 1200 kg fine aggregate and 1 kg water reducer as raw materials. The preparation method of the cement mortar is as follows: ordinary Portland cement and fine sand are weighed, added into a mixing tank, and dry mixed for 10 min to obtain dry mixed mortar; 420 kg water is poured into the dry mixed mortar and fully stirred to obtain cement mortar for lining of ductile iron pipes.
[0066] Test example: Performance test of cement mortar
[0067] Referring to the "Method for Determining the Fluidity of Cement Mortar" in GB / T 2419-2005 and the "Method for Testing the Strength of Cement Mortar (ISO Method)" in GB / T 17671-2021, the compressive strength and flexural strength of the cement mortars prepared in the above embodiments and comparative examples were tested; and the crack defect rates of mortars with different components were visually inspected and counted. The test results are shown in Table 2 below.
[0068] Table 2 Cement mortar performance test results
[0069] It can be seen from the test results in Table 2 above that the cement mortar for ductile iron pipe lining of Examples 1-3 has high fluidity and good water retention performance. The lining materials of Examples 1-3 add fly ash accounting for 10-15% of the cement dosage, and add nano-silicon composite accounting for 5-10‰ of the cement dosage, which can greatly improve the compressive strength and flexural strength of the cement mortar. The lining materials of Examples 1-3 can significantly reduce the crack defect rate of the mortar coating lining through the synergistic combination of fly ash, nano-silicon composite and.
[0070] The performance of the cement mortar prepared in Comparative Example 1 is much worse than that of Examples 1 and 2. This shows that only when the nano-lithium silicate and silica sol are modified by silane coupling agent in advance and then mixed with other raw materials, can the fluidity, workability and mechanical properties of the cement mortar be maximized and the crack defect rate of the mortar coating lining be reduced when used as the lining material of the ductile iron pipe. Since the cement mortar raw materials of Comparative Example 2 lack fly ash, the cement mortar raw materials of Comparative Example 3 lack nano-silicon composites, and the cement raw materials of Comparative Example 4 lack fly ash and nano-silicon composites, the mechanical properties such as flexural strength and compressive strength are affected, and the crack defect rate of the coating lining is high.
[0071] According to the test examples, the cement mortar for ductile iron pipe lining of the present invention has the characteristics of high fluidity and good water retention, which is conducive to the uniform distribution of the material on the inside of the pipe; and the cement mortar also has high compressive strength and flexural strength, and a low mortar coating lining crack defect rate.
[0072] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A cement mortar for lining of ductile iron pipe, characterized in that: The composition comprises, by weight, 1000 parts of cement, 1200-2100 parts of fine aggregate, 100-150 parts of fly ash, 5-10 parts of nano-silicon compound and 1-2 parts of water reducing agent; The nano-silicon composite is prepared by mixing nano-lithium silicate and silica sol in a mass ratio of (0.05-0.3):1, and adding 1-2% of ethanol and 1-5% of silane coupling agent to form an in-situ modification.
2. The cement mortar for ductile iron pipe lining according to claim 1, characterized in that: The mass ratio of the nano-lithium silicate to the silica sol is 0.2:
1.
3. The cement mortar for ductile iron pipe lining according to claim 1, characterized in that: The preparation method of the nano-silicon composite is as follows: adding the nano-lithium silicate to the silica sol and mixing evenly, adding ethanol and a silane coupling agent, and keeping the mixture at 45-60° C. for 2-3 h to obtain the nano-silicon composite.
4. The cement mortar for ductile iron pipe lining according to claim 3, characterized in that: In the preparation method of the nano-silicon composite, the nano-silicon composite is obtained by keeping the temperature at 50° C. for 2 h.
5. The cement mortar for ductile iron pipe lining according to claim 1, characterized in that: The cement is ordinary Portland cement with a P.O. of 42.5 and / or a P.O. of 52.
5.
6. The cement mortar for ductile iron pipe lining according to claim 1, characterized in that: The fly ash is Class II fly ash, which is Class F Class II fly ash in GB / T 1596-2017.
7. The cement mortar for ductile iron pipe lining according to claim 1, characterized in that: The water reducer is one or more of lignin sulfonate sodium salt, naphthalene-based high-efficiency water reducer, aliphatic high-efficiency water reducer, amino high-efficiency water reducer and polycarboxylic acid high-efficiency water reducer.
8. The method for preparing cement mortar for ductile iron pipe lining according to any one of claims 1 to 7, characterized in that: The cement, fly ash, fine aggregate and water reducing agent are uniformly mixed to obtain a dry mixture; the nano-silicon composite is added with water and stirred to obtain a nano-silicon composite solution; the nano-silicon composite solution is added to the dry mixture to obtain cement mortar for ductile iron pipe lining; The amount of water added for preparing the nano-silicon composite solution is 0.35-0.5 times the mass of the cement.